Internalization of Escherichia Coli O157:H7 by Bovine Rectal Epithelial Cells - Sheng, Haiqing; Wang, Jing; Lim, Ji Youn; Davitt, Christine; Minnich, Scott A.; Hovde, Carolyn J. (Frontiers in Microbiology, 2011)
Escherichia coli O157:H7 (O157) causes human diarrheal disease and healthy cattle are its primary reservoir. O157 colonize the bovine epithelial mucosa at the recto-anal junction (RAJ). Previous studies show that O157 at this site are not eliminated by aggressive interventions including applications of O157-specific lytic bacteriophages and other bactericidal agents. We hypothesize that some O157 at the RAJ mucosa are protected from these killing agents by host cell internalization. To test this hypothesis, rectal biopsies from O157 culture positive and negative cattle were analyzed by fluorescent microscopy and subjected to gentamicin protection assays. GFP-labeled bacteria were found located deep within the tissue crypts and a small number O157 were recovered from rectal biopsies after gentamicin treatment. Primary bovine rectal epithelial (PBRE) cell cultures were incubated with O157 and subjected to gentamin protection assays. Strains ATCC 43895, 43894, Sakai and WSU180 entered the PBRE cells with different levels of efficiency ranging from 0.18% to 25% of the inocula. Intracellular bacteria were confirmed to be within membrane-bounded vacuoles by electron microscopy. Cytocalasin B curtailed internalization of O157 indicating internalization was dependent on eukaryotic microfilament assembly. Strain ATCC 43895 exhibited the highest efficiency of internalization and survived for at least 24 h within PBEC cells. Deletion mutation of intimin, its receptor, or Shiga toxin in ATCC 43895 did not reduced bacterial internalization. This strain produced more biofilm than the others tested. Retrospective analysis of cattle challenged with two O157 strains, showed ATCC 43895, the most efficient at host cell internalization, was most persistent.